A rare case of Buschke–Löwenstein tumor in HPV-negative patient (Dermatology Reports, 2020)
Buschke–Löwenstein tumor is known to manifest not only in sexually active people and adolescents exposed to violence or drugs, but also in people who do not have any predisposing factors or bad habits. Several studies have shown that in the majority of children with anogenital warts, HPV can be transmitted asexually by hetero- inoculation or through infected objects. To our knowledge, there are currently few reports on BLT in HPV-negative patients in the literature. In our case, the patient presented early, with multiple slow growing warts, no history of alcohol intake, drug use or smoking and no HPV infection, which makes this case unique and important.